The effect of SOX on small auditor exits and audit quality - DeFond, Mark L.; Lennox, Clive S. (Journal of Accounting and Economics, 2011)
We find that over six hundred auditors with fewer than 100 SEC clients exit the market following SOX. Compared to the non-exiting auditors, the exiting auditors are lower quality, where quality is gauged by: (1) avoidance of AICPA peer reviews and failure to comply with PCAOB rules, and (2) severity of the peer review and inspection reports. In addition, clients of exiting auditors receive higher quality auditing from successor auditors, as captured by a greater likelihood of receiving going concern opinions. Our results suggest that the PCAOB inspections improve audit quality by incentivizing low quality auditors to exit the market.